Primary prevention of ischaemic heart disease - Hobbs, F (2006)
Cardiovascular disease (CVD) remains the leading cause of global morbidity and mortality causing over 4 million deaths in Europe and 17 million deaths worldwide in 1999. Coronary heart disease (CHD) is the primary killer of Americans, accounting for 1 in 5 deaths in 2000. Abnormal lipids, smoking, hypertension, diabetes, abdominal obesity, psychosocial factors, low consumption of fruit and vegetables, no alcohol intakes and irregular physical exercise account for more than 90% of the risk of an acute myocardial infarction (MI) across age groups and in all regions of the world, according to the recent INTERHEART study. Since cardiovascular disease (CVD) is therefore a multi-factorial syndrome, guidelines need to identify risk ands provide preventative and treatment goals, whilst remaining simple to interpret and implement. The National Cholesterol Education Program (NCEP), Adult Treatment Panel (ATP) III guidelines and the Third Joint Task Force of European Societies guidelines both recognise the importance of dyslipideamia, hypertension and smoking as the main risk factors for CVD, advocate risk assessment based on the Framingham Algorithm to determine those eligible for primary prevention, and the role of lifestyle changes, statin and anti-hypertensive therapies as the most evidence-based interventions. © 2006 Elsevier Ltd. All rights reserved.